Counter-complementarity control of the weak exchange interaction in a bent {Ni(ii)3} complex with a μ-phenoxide-μ-carboxylate double bridge. (3rd October 2019) - Fiorini, Guillermo; Carrella, Luca; Rentschler, Eva; Alborés, Pablo
Abstract : We report a combined computational and experimental study of a weak exchange interaction in a bent {Ni(ii )3 } complex controlled by counter-complementarity. Abstract : We have prepared and structurally characterized a novel Ni3 bent complex bearing a double μ-phenoxide-μ-carboxylate bridge. Both terminal Ni(ii ) sites are symmetry related, offering a simplified exchange interaction scheme. DC magnetic data is consistent with a weak antiferromagnetic interaction between the central and terminal Ni(ii ) ions. As expected for a Ni(ii ) system, local zero-field splitting is observed, which can be experimentally established. Broken symmetry quantum chemical calculations, as well as ab initio CASSCF-SA-SOC computations that support the magnetic experimental data, were also performed. From the analysis of other reported closely related Ni(ii ) systems, a counter-complementarity effect exerted by the carboxylate bridge is proposed, which might explain the weaker exchange interactions compared to those observed in double μ-phenoxide bridged Ni(ii ) compounds.